Ultrathin waterborne acoustic metasurface for uniform diffuse reflections. (1st June 2023) - Liang, Tianbao; He, Mu; Dong, Hao-Wen; Xia, Liang; Huang, Xiaodong
Abstract: Achieving efficient wave manipulations with ultrathin metasurfaces at low frequencies less than 1000 Hz is a challenging research subject, especially for underwater scenes. This work proposes a novel design strategy for ultrathin and highly efficient waterborne reflective pentamode metasurfaces to realize uniform diffuse reflections. To this end, a theoretical model that eases off the demand on the impedance matching is first established for plane waves impinging on an interface layer, and an ideal diffusion field is subsequently constructed. Secondly, the spatially variant equivalent impedances of the metasurface are identified, and their corresponding pentamode material configurations are designed inversely with band structure analyses. Numerical results show that the normalized diffusion coefficient can reach up to 0.81 at the targeted frequency 288 Hz, while the thickness of the designed metasurface is limited to several centimeters, only one hundredth of the working wavelength. Further verifications reveal that the metasurface applies also to a broader frequency range from 200 Hz to 650 Hz. The strategy paves potentially the way towards acoustic wave manipulations of ultrathin waterborne metasurfaces at deep-subwavelength scale.